Aqidah Education Produces an Integrative Model of Moral Formation: Pendidikan Akidah Menghasilkan Model Integratif Pembentukan Akhlak - Alamsyah, Dani; Hidayatullah, Syarif; Arif, Mahmud (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Moral decline among students raises critical concerns regarding the adequacy of current character education approaches. Specific Background Within Islamic pedagogy, moral formation is inseparable from theological foundations, where aqidah constitutes the core basis shaping ethical behavior. Knowledge Gap Existing studies predominantly emphasize pedagogical strategies while overlooking the epistemological and theological linkage between faith and moral development, and lack an integrated framework bridging classical Islamic thought with contemporary moral education discourse. Aims This study aims to synthesize classical and contemporary perspectives to construct an integrative conceptual model connecting aqidah and akhlak through an integrative literature review. Results The findings reveal that aqidah functions as a comprehensive meaning system shaping worldview, moral awareness, and value orientation, where akhlak emerges as an internalized manifestation rather than externally imposed norms. The study formulates an integrative model positioning aqidah as the foundation, moral awareness as the mediating process, and akhlak as observable behavioral expression. Novelty The study offers a systematic conceptual mechanism linking theological belief with moral behavior, addressing fragmentation in prior research. Implications The findings suggest that aqidah-based education requires contextual learning, teacher modeling, and sustained value practice to ensure authentic character formation. Highlights• Integrative model connects theological belief, moral awareness, and behavioral expression• Moral conduct emerges from internalized faith rather than external regulation• Conceptual synthesis bridges classical Islamic thought with contemporary moral discourse KeywordsAqidah Education; Moral Character; Akhlak; Islamic Education; Integrative Review